2016
DOI: 10.1186/s13071-016-1673-4
|View full text |Cite
|
Sign up to set email alerts
|

Ticks infesting domestic dogs in the UK: a large-scale surveillance programme

Abstract: BackgroundRecent changes in the distribution of tick vectors and the incidence of tick-borne disease, driven variously by factors such as climate change, habitat modification, increasing host abundance and the increased movement of people and animals, highlight the importance of ongoing, active surveillance. This paper documents the results of a large-scale survey of tick abundance on dogs presented to veterinary practices in the UK, using a participatory approach that allows relatively cost- and time-effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
136
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 113 publications
(144 citation statements)
references
References 34 publications
8
136
0
Order By: Relevance
“…The inspected animals were dogs that were collected from Cairo province and camels which were collected from Cairo, Giza, and Sinai provinces. These animals were examined for the presence of ticks in neck, chest area, and around the soft parts of their bodies such as the inner sides of the hind and forelegs, perineal area, inner surface of ears and udders [58]. …”
Section: Methodsmentioning
confidence: 99%
“…The inspected animals were dogs that were collected from Cairo province and camels which were collected from Cairo, Giza, and Sinai provinces. These animals were examined for the presence of ticks in neck, chest area, and around the soft parts of their bodies such as the inner sides of the hind and forelegs, perineal area, inner surface of ears and udders [58]. …”
Section: Methodsmentioning
confidence: 99%
“…For instance, I. crenulatus was considered to occur in western, central and eastern Europe [7]. However, recent studies on ticks from carnivores confirmed its presence in Romania [8], but not in central and western Europe [911]. Furthermore, the validity of I. crenulatus was questioned because of its uninformative description that often results in it being misidentified as I. hexagonus [12].…”
Section: Introductionmentioning
confidence: 99%
“…Ixodes hexagonus and I. canisuga are common species on carnivores in the western Palaearctic [3, 11, 15–17]. While I. hexagonus can also be found in eastern Europe [8, 9, 14], I. canisuga occurs predominantly in western and central Europe [9, 18, 19].…”
Section: Introductionmentioning
confidence: 99%
“…UK veterinary practitioners are increasingly alerted to the threats from exotic ticks and tickborne pathogens, aided by high profile surveillance such as the Big Tick Project,1 promotional activities by ESCCAP UK and Ireland and Public Health England’s Tick Surveillance Scheme. Ongoing awareness is essential and valuable online resources exist for identifying male and female ticks (eg, the Bristol Tick ID website ).…”
mentioning
confidence: 99%